Aro katimyas da! a memory album of titled Kapampangan beauties (1908 - 2012) - Castro, Alex R. ([Angeles City] Center for Kapampangan Studies, Holy Angel University, 2012)
An annotated pictorial album of more than 200 faces of Kapampangan beauties, from the fabled carnival era to pageants of contemporary times, enriched with short biographical sketches and rare vintage photographs.
Includes bibliographical references (pages 239-240) and index.
Keywords: Beauty contestants -- Philippines -- Pampanga -- Pictorial works; Beauty contests -- Philippines -- Pampanga -- Pictorial works; Pampangan (Philippine people) -- Social aspects -- Philippines